Investing in an Olympic agenda: from Rio to Tokyo and beyond - Russo, Eduardo; Figueira, Ariane Roder; Mataruna-Dos-Santos, Leonardo Jose (Frontiers in Sports and Active Living, 2025)
ContextThis study was inspired by the considerable risks and diminishing enthusiasm among societies to invest in Olympic agendas, which traditionally involve billions of dollars, various opportunities, and complexities for host countries.PurposeThe objective of this study was to evaluate the risks and benefits of long-term equity investments for companies and governments engaged in the Olympic movement.MethodQualitative methodologies were employed for this research, utilizing a multi-case approach that included 38 comprehensive interviews with companies and entities impacted by the Rio 2016 and Tokyo 2020 Olympic Games.ResultsConsequently, a theoretical framework titled “Risks and Opportunities Related to Olympic Investments” is presented to elucidate the dynamics of investment flows, competitive pressures in specific sectors, and future threats and trends for the Olympic movement.FindingsThe research revealed that the gigantism of past editions exerted significant pressure on organizers and companies to adopt new management practices and enhance investment planning, striving for minimal environmental impact and long-term economic sustainability. These insights aid scholars, practitioners, and policymakers in making informed decisions about resource allocation in Olympic contexts, and highlight the necessity for updated strategic frameworks to ensure the viability and positive impact of future Olympic Games.